2018
DOI: 10.1002/oby.22310
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch in Children’s Weight Assessment, Ideal Body Image, and Rapidly Increased Obesity Prevalence in China: A 10‐Year, Nationwide, Longitudinal Study

Abstract: Objectives: This study examined secular trends in children’s weight status assessment, measured weight status and ideal body image, and their associations with subsequent changes in BMI, and it explored the differences between sociodemographic groups in China. Methods: Longitudinal data from the China Health and National Survey of 4,605 children aged 6-17 collected during 2000-2011 were used and fitted to mixed models. Results: Overweight/obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
16
0
3
Order By: Relevance
“…stunting. e findings are consistent with the literature as studies suggest overweight or obesity is more prevalent in urban than in rural areas [32][33][34][35], trends uncommon across the globe, and unique to the country of China. Surprisingly, subjects in a small-medium city had the highest rate of underweight and second-highest rate of overweight or obesity.…”
Section: Discussionsupporting
confidence: 90%
“…stunting. e findings are consistent with the literature as studies suggest overweight or obesity is more prevalent in urban than in rural areas [32][33][34][35], trends uncommon across the globe, and unique to the country of China. Surprisingly, subjects in a small-medium city had the highest rate of underweight and second-highest rate of overweight or obesity.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing prevalence of negative perception of the body image was reported in Chinese children, with more rapid increases of taking weight management behaviours in adolescents, as well as in girls versus boys [16,17]. However, few studies have been conducted nationwide involving pupils and incorporating both body image dissatisfaction and self-perceived weight status together in terms of body perception.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the documents were produced within the last 20 years, with over 80% being published in the recent ten years. This can be explained by the rapid increase in the prevalence of CHO in china, which has almost tripled just within the last two decades [4]. This has resulted in increased attention being given to addressing CHO, which is re ected in research output.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, the prevalence of CHO in China has gradually increased, now almost equal to that in developed countries [1,3]. Between 2000 and 2011, the prevalence of CHO in China nearly tripled from 6.5-16.8% [4].…”
Section: Introductionmentioning
confidence: 99%